Perlindungan Hukum terhadap UMKM dari Praktik Monopoli dan Persaingan Usaha Tidak Sehat di Era Digital - Ida Ayu Putu Gita Prayascita (Jurnal Hukum dan Sosial Politik, 2025)
The purpose of this paper is to examine the legal protection provided to MSMEs through Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, and the role of the Business Competition Supervisory Commission (KPPU) in upholding justice in the digital sector. This research uses a normative legal approach with an analysis of primary, secondary, and tertiary legal materials. The results of the study indicate that various obstacles remain in the implementation of legal protection for MSMEs, ranging from low digital literacy to the imbalance of power between MSMEs and large digital platforms. Therefore, regulatory strengthening and policy reform are needed that are responsive and pro-MSME to create a fair, inclusive, and sustainable digital business ecosystem.